2013
DOI: 10.1111/jcpe.12192
|View full text |Cite
|
Sign up to set email alerts
|

Number of teeth, C‐reactive protein, fibrinogen and cardiovascular mortality: a 15‐year follow‐up study in a Finnish cohort

Abstract: Aim(s) To test whether the number of teeth, an inverse proxy for composite oral infection scores is associated with better survival. Materials and Methods The Kuopio Oral Health and Heart study initiated a case-control study in 1995–1996 consisting of 256 consecutive coronary artery disease patients and 250 age and gender matched controls. We appended the mortality data and formulated a longitudinal study. By May 31st, 2011, 124 mortalities had occurred and 80 of which were of cardiovascular origin. Using Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 54 publications
1
56
1
1
Order By: Relevance
“…However, the simulated data have proven that the ‘time to event analyses’ such as Cox proportional hazard regressions which use semi‐nonparametric method were unaffected by the high CAD proportion at baseline (Janket et al . ). Therefore, the results from the present study can be generalized to other populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the simulated data have proven that the ‘time to event analyses’ such as Cox proportional hazard regressions which use semi‐nonparametric method were unaffected by the high CAD proportion at baseline (Janket et al . ). Therefore, the results from the present study can be generalized to other populations.…”
Section: Discussionmentioning
confidence: 97%
“…), and the contribution of oral infection to CVD was mediated in part via CRP (Janket et al . ). Therefore, oral inflammation and CRP are in a confounding relationship.…”
Section: Introductionmentioning
confidence: 97%
“…), and reported that the mortality risk increased while the NT decreased (approximately 7 fold higher risk when the number of teeth <10 than >25). Janket 23 have reported that the CVD survival was ameliorated 27% in every increase of 10 teeth. Zanella 24 have recently reported that tooth loss was significantly associated with a higher chance of having at least one obstructed vessel and with vessel obstruction ≥ 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Acute oral infections have been shown to be correlated with increased serum inflammatory markers such as C-reactive protein which trigger systemic reactions that could be used as predictors of mortality and indicators of prognoses of diseases. 2 Another valid point worth mentioning is that individuals with fewer teeth, looser teeth or unstable dentures have poorer masticatory ability and nutrient intake, parameters that are usually associated with increased mortality among elderly populations. 4 Oral infections can play a prominent role in the development and pathogenesis of many systemic diseases not only in ill or immune-compromised individuals but in healthy ones as well.…”
Section: Dental Infections May Have Detrimental Consequencesmentioning
confidence: 99%